The Effect of Unintended Pregnancy Among Married Women on the Length of Breastfeeding in Indonesia - Lia suryani; Amrina Rosyada (Faculty of Public Health, Sriwijaya University, 2020)
The coverage of exclusive breastfeeding in Indonesia in 2017 is 35%, far below the recommendations of WHO (World Health Organization) of 50%. This rate is getting lower in unwanted pregnancies. Every year there is13.3% incidence of unwanted pregnancy in women aged 15-44 years. It has an impact on the mental, psychological condition of the mother in the process of child care and nutrition from birth. This study aims to determine the prevalence and relationship of unwanted pregnancy among married women on the duration of breastfeeding in Indonesia. This research wa a quantitative study using cross -sectional study design, a sample of 5,163 married women, and aged 15-49 years. Data were analyzed using univariate descriptive statistics on complex sample analysis, bivariate analysis using Chi-Square, and multivariate using logistic regression tests of risk factor models. This study showed that 1,267 mothers who breastfed <6 months and there was a relationship between the unwanted pregnancy with the duration of breastfeeding (p-value: 0.007 with PR: 1.349; 95% CI: 1.085-1.676) after been controlled by the use of contraception. The support of husband and health workers during pregnancy, childbirth until child care is needed to support breastfeeding.